Psychometric properties of dual-task balance assessments for older adults: A systematic review. Issue 4 (April 2015) - Yang, L.; Liao, L.R.; Lam, F.M.H.; He, C.Q.; Pang, M.Y.C.
Highlights The reliability of gait parameters under dual-task conditions is generally good. The reliability of cognitive outcomes and dual-task cost is generally poor to fair. The usefulness of dual-task balance assessments in fall prediction is inconclusive. The methodological quality of majority of the studies reviewed is poor or fair.